2018
DOI: 10.1121/1.5078770
|View full text |Cite
|
Sign up to set email alerts
|

Effects of signal bandwidth and noise on individual speaker identification

Abstract: Two experiments were conducted to evaluate the effects of increasing spectral bandwidth from 3 to 10 kHz on individual speaker recognition in noisy conditions (+5, 0, and −5 dB signal-to-noise ratio). Experiment 1 utilized h(Vowel)d (hVd) signals, while experiment 2 utilized sentences from the Rainbow Passage. Both experiments showed significant improvements in individual speaker identification in the 10 kHz bandwidth condition (6% for hVds; 10% for sentences). These results coincide with the extant machine re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…(3) Given the findings of this study and previous behavioral findings demonstrating the benefits of extending the bandwidth from 3 to 10 kHz for identifying a talker of interest in noise (Schwartz et al, 2018), it is important to consider how speech processing algorithms designed to amplify the high-frequency region of speech (e.g., frequency-lowering techniques) potentially alter natural acoustic cues regarding talker identity [for a review of frequency-lowering techniques, refer to Alexander (2013)]. In noisy conditions where low frequencies are significantly masked by environmental noise, the information above 3-4 kHz may increase in importance.…”
Section: Discussionmentioning
confidence: 74%
See 1 more Smart Citation
“…(3) Given the findings of this study and previous behavioral findings demonstrating the benefits of extending the bandwidth from 3 to 10 kHz for identifying a talker of interest in noise (Schwartz et al, 2018), it is important to consider how speech processing algorithms designed to amplify the high-frequency region of speech (e.g., frequency-lowering techniques) potentially alter natural acoustic cues regarding talker identity [for a review of frequency-lowering techniques, refer to Alexander (2013)]. In noisy conditions where low frequencies are significantly masked by environmental noise, the information above 3-4 kHz may increase in importance.…”
Section: Discussionmentioning
confidence: 74%
“…Segmental information related to phoneme and sentence recognition (e.g., Donai and Paschall, 2015;Vitela et al, 2015) as well as indexical features of the talker, such as sex (e.g., Monson et al, 2014;Donai and Lass, 2015;Donai and Halbritter, 2017) and talker identity (Schwartz et al, 2018), have also been found in the high-frequency region of the speech signal. Some studies limited auditory access only to high-frequency energy (HFE) above 3-5 kHz (e.g., Donai and Paschall, 2015;Donai and Halbritter, 2017;Monson et al, 2014;Vitela et al, 2015), while others varied the spectral bandwidth of the stimuli to purposely include or exclude HFE above 8 kHz (e.g., Schwartz et al, 2018, Flaherty et al, 2021Polspoel et al, 2022).…”
Section: Introductionmentioning
confidence: 99%